2022
DOI: 10.7759/cureus.22707
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Closed Reduction With Percutaneous Pinning and Open Reduction With Internal Fixation in the Operative Management of Pediatric Type III Supracondylar Fractures

Abstract: BackgroundSupracondylar fracture with total displacement is classified as Gartland type 3. The operative management for this type of fracture can be closed reduction with percutaneous pinning (CRPP) or open reduction with internal fixation (ORIF). This study aims to determine whether CRPP or ORIF led to smaller changes in Baumann's angle, the carrying angle, loss of motion, and complication when treating pediatric supracondylar fractures. MethodologyIn a retrospective cohort design, pediatric patients presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…There was a significant difference comparing the two groups' methods in this study (p = 0.038). 11 Yaokreh et al, and Bahadur et al, found no significant difference between CRPP and ORIF. Yaokreh et al achieved 90.9 % versus 92 % satisfaction; P = 0.8835.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…There was a significant difference comparing the two groups' methods in this study (p = 0.038). 11 Yaokreh et al, and Bahadur et al, found no significant difference between CRPP and ORIF. Yaokreh et al achieved 90.9 % versus 92 % satisfaction; P = 0.8835.…”
Section: Discussionmentioning
confidence: 92%
“…10 The loss of carrying angle was less than 5 degrees in all incidents, as demonstrated by Bahadur et al However, in the Abousaleh et al study, in the ORIF group, the loss of carrying angle was less (4.23 degrees) than in the CRPP group (5.51 degrees), with a statistically significant p = 0.023. 11 According to Shrestha et al, the mean Bauman's angle for the CRPP and ORIF groups was 16.89 and 18.88 degrees, respectively. Between CRPP and ORIF, significant difference (P = 0.142).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Neither method demonstrated a significant advantage over the other [ 3 ]. However, studies showed significantly better outcomes for children with Gartland type 3 SCH fractures treated with ORIF, reinforcing ORIF’s superiority over CRPP, albeit these studies had limited sample sizes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most vulnerable age been 4 to 11 years with 85% of the children to be suffering from supracondylar fracture. 1 Majority of these children have gender biased with male children been more vulnerable to fall and accidents than female children. [2][3][4] Children with SH fractures have a high risk of complicated fractures which required high skills for treatment.…”
Section: Introductionmentioning
confidence: 99%